Perceived social support and financial well-being as predictors of quality of life among prison inmate spouses in Ogun state (2020)
Over the years, the increase in numbers of prison inmates and the detrimental effect of incarceration on the families and society at large have raised severe attention and concern. Studies have documented the effects of incarceration and some psychological factors of prison inmates but there is a dearth of research on quality of life among spouses of prison inmates. This study, therefore, investigated perceived social support and financial well-being as predictors of quality of life among prison inmate spouses in Ogun State. Descriptive cross- sectional survey research design was adopted, utilizing a purposive sampling technique to select the participants across correctional centres in Ogun State. A total of 281 spouses of prison inmates with mean age of 41.6yrs and SD (11.2) participated in the study. Self report questionnaires measuring quality of life (.69), perceived social support scale (76) and financial wellbeing scale (.77) were used for data collection. Three hypotheses were tested using appropriate statistics. Findings revealed a significant relationship between perceived social support and quality of life (r = .22; p<.01) and between financial wellbeing and quality of life (r = .54; p<.01). Also, financial well-being and perceived social support jointly contributed 5% variance in quality of life (R = .23; R2 = .05; F (2, 279) = 4.66; P<.05); further analysis revealed that financial well-being (β = .23; t= 3.53; p<05) and perceived social support (β = .19; t= 2.76; p<.05) independently predicted quality of life. It was concluded that perceived social support and financial well-being were significant correlates of quality of life. Based on these findings, it was recommended that, relations and friends should provide adequate psychosocial and financial supports for spouses of prison inmates to preserve and strengthen positive family connections, promote the quality of life and ensure a healthy society